Efficacy and safety of PCSK9 monoclonal antibodies. Issue 12 (2nd December 2019) - Iqbal, Zohaib; Dhage, Shaishav; Mohamad, Jamal Basheer; Abdel-Razik, Alaa; Donn, Rachelle; Malik, Rayaz; Ho, Jan Hoong; Liu, Yifen; Adam, Safwaan; Isa, Basil; Stefanutti, Claudia; Soran, Handrean
ABSTRACT: Introduction : Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are novel drugs that have been developed since the discovery of the PCSK9 protein in 2003. In addition to background statin treatment, they reduce low-density lipoprotein cholesterol (LDL-C) to unprecedented levels and have shown encouraging results in improving cardiovascular events. Concerns regarding the safety of PCSK9 inhibitors and very low LDL-C have somewhat been allayed after several longer-term prospective studies. Areas covered : A comprehensive literature search was carried out including article searches in electronic databases (EMBASE, PUBMED, OVID) and reference lists of relevant articles. This review examines novel research concerning PCSK9 monoclonal antibodies and cardiovascular outcomes with a special focus on their safety and tolerability. The safety of very low LDL-C concentrations and the link between LDL-C lowering and diabetes is also discussed. Expert opinion : PCSK9 monoclonal antibodies when added to background statin therapy, lowers LDL-C to previously unattainable levels. This is safe with little undesirable effects and impacts positively on cardiovascular disease. Current guidance limits their use to primary prevention. Cost effectiveness should be taken into consideration before allowing a wider use of this new class of cholesterol lowering therapy and more data on their long-term safety is welcome.